2003
DOI: 10.1038/sj.bjc.6600925
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the actions of bisphosphonate zoledronic acid in breast cancer cells by dual RhoA-dependent and -independent effects

Abstract: Zoledronic acid (ZOL) is a nitrogen-containing bisphosphonate and its use in reducing osteoporosis and cancer-induced osteolysis is increasing. Recent findings indicated that ZOL has a direct effect on cancer cells. In this study, the effect of ZOL was examined on the aggressive MDA-MB-231 breast cancer cell line. ZOL induces an important inhibition of cell invasion at low concentrations (1 mM). This is not explained by modifications of proteases involved in cell invasiveness (matrix metalloproteinases and uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
110
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(124 citation statements)
references
References 44 publications
(50 reference statements)
8
110
1
4
Order By: Relevance
“…These observations are in agreement with those of Denoyelle and colleagues 33 in breast cancer cells. As in case of the cytotoxic effect, the microfilament activity of ZOL was also blocked by addition of GGOH, but not FOH.…”
Section: Discussionsupporting
confidence: 83%
“…These observations are in agreement with those of Denoyelle and colleagues 33 in breast cancer cells. As in case of the cytotoxic effect, the microfilament activity of ZOL was also blocked by addition of GGOH, but not FOH.…”
Section: Discussionsupporting
confidence: 83%
“…The present study demonstrated that FTI-277 effectively inhibited the invasive/migratory phenotypes of H-Ras-MCF10A and Hs578T cells, but not those of MDA-MB-231 cells. Consistent with these results, a previous study observed that FTI-277 did not inhibit the Transwell invasion of MDA-MB-231 cells (36). By contrast, it has been reported that the transendothelial invasion of MDA-MB-231 cells was mildly inhibited by FTI-277 (33).…”
Section: Discussionsupporting
confidence: 80%
“…Using an intermediary of this pathway (GGOH), apoptosis was reduced by 50% for cells treated with the sequence ' letrozole then ZA'. Inhibition of the mevalonate pathway by nitrogen-bisphosphonates is integral for inducing a variety of effects including apoptosis of osteoclasts (Amin et al, 1992), breast cancer cells (Jagdev et al, 2001), prostate cancer cells (Oades et al, 2003), myeloma cells (Shipman et al, 1998) and inhibition of tumour cell invasion (Denoyelle et al, 2003). Furthermore, inhibition of this pathway also contributes to the apoptosis induced when breast (and prostate) cancer cells are treated in combination with ZA and doxorubicin (Neville-Webbe et al, 2005), or when breast cancer cells are treated with ZA and paclitaxel (Neville-Webbe et al, 2006).…”
Section: Discussionmentioning
confidence: 99%